2009
DOI: 10.1080/10398560802579526
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrically Impaired Medical Practitioners: Better Care to Reduce Harm and Life Impact, with Special Reference to Impaired Psychiatrists

Abstract: Prevention, early detection, intervention, and treatment programs that are more continuous more sensitive to the needs of impaired practitioners, that are more continuous, better structured, and rehabilitation and recovery focused, may be more likely to produce a positive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Reports indicate that while HCPs often witness incompetence or disrespect in the work‐place, very few choose to discuss their concerns with the problematic co‐worker or the relevant supervisor . Perhaps a multi‐faceted solution as suggested by Rosen and Trafinow is warranted, incorporating prevention, ‘speaking out’ in combination with mandatory drug testing and structured rehabilitation programmes for addicted HCPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that while HCPs often witness incompetence or disrespect in the work‐place, very few choose to discuss their concerns with the problematic co‐worker or the relevant supervisor . Perhaps a multi‐faceted solution as suggested by Rosen and Trafinow is warranted, incorporating prevention, ‘speaking out’ in combination with mandatory drug testing and structured rehabilitation programmes for addicted HCPs.…”
Section: Discussionmentioning
confidence: 99%
“…Following drug rehabilitation, abstinence rates for physicians greatly exceed that of the general public, with success rates of between 74 and 90% . This is especially true for opioid dependence, where HCPs have remarkably better outcomes than other groups following opioid‐treatment programmes . The fundamental problem is that access to, and use of, controlled drugs are commonplace among many HCPs, particularly in anaesthesiology where the abstinence rate following drug rehabilitation is substantially lower .…”
Section: Introductionmentioning
confidence: 99%
“…One to two percent may be unsafe, while 5-12 percent may not be practising at an acceptable level. [4][5][6][7] Minor degrees of burnout can affect approximately one-third of all doctors at some stage of their career. 8 Rates of burnout are difficult to estimate due to under reporting.…”
Section: Assessment Of the Problemmentioning
confidence: 99%
“…8 Rates of burnout are difficult to estimate due to under reporting. 9 When a doctor is considered unsafe to work, it is generally a result of either physical [10][11][12] or mental health illness (including burnout and stress, [13][14][15][16][17][18][19] anxiety, depression and suicidal tendencies, 2,5,8,16,18 substance abuse and dependency, 14,20 or cognitive impairment). 21,22 An Australian review of complaints found that doctors with cognitive impairment started receiving complaints made against them and had inappropriately been prescribing drugs of abuse for ~10 years before the diagnosis of cognitive impairment is being made.…”
Section: Assessment Of the Problemmentioning
confidence: 99%
“…27,28 The same can be surmised for practicing ACPs who face potential loss of reputation and livelihood if they seek help. 29,30 Denial is a common component of SUD, and it is not necessarily limited to the addicted person. Colleagues of an affected individual often do not recognize behaviour that, in retrospect, may have been obvious.…”
Section: Identificationmentioning
confidence: 99%